A Bibliometric Analysis of Nanocrystalline Cellulose Production Research as Drug Delivery System Using VOSviewer - Allifya Fauziah (Indonesian Journal of Multidiciplinary Research, 2022)
Nanocrystalline cellulose (NCC) has a superiority due to its biocompatibility and biodegradability whose increases the interest of researchers in the field of nanotechnology, especially in drug delivery systems. The purpose of this study is to conduct bibliographical analysis in nanocrystalline cellulose production and its application as a drug delivery system, that combines mapping analysis with VOSviewer software. The reference manager application was used to retrieve survey data. The data obtained is the result of searching for the keyword "nanocrystalline cellulose, drug delivery system". Publish articles related to the topics found as many as 1000 articles between 2017 and 2021. The results showed that nanocrystalline cellulose production research as a drug delivery system increased from 2017 to 2019, but decreased in 2020 to 2021. This study is expected to help researchers carry out and determine targeted research topics and serve as a reference.